2022
DOI: 10.3389/fpsyg.2022.765312
|View full text |Cite
|
Sign up to set email alerts
|

Parental Reflective Functioning and Its Association With Parenting Behaviors in Infancy and Early Childhood: A Systematic Review

Abstract: BackgroundParental reflective functioning (PRF) refers to parents’ mental capacity to understand their own and their children’s behaviors in terms of envisioned mental states. As part of a broader concept of parental mentalization, PRF has been identified as one of the central predictors for sensitive parenting. However, the unique contribution of PRF to the quality of various parenting behaviors has not yet been addressed systematically. Thus, the present article provides a systematic overview of current rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 97 publications
0
22
0
Order By: Relevance
“…Stuhrmann et al. (2022) suggested that the PDI has a relational focus on more dynamic aspects of the parent–child relationship, whereas the PRFQ captures generic key features of the parental mentalizing process. The findings of the study reported here provide further caution against conflating research findings from the two PRF measures.…”
Section: Discussionmentioning
confidence: 99%
“…Stuhrmann et al. (2022) suggested that the PDI has a relational focus on more dynamic aspects of the parent–child relationship, whereas the PRFQ captures generic key features of the parental mentalizing process. The findings of the study reported here provide further caution against conflating research findings from the two PRF measures.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of evidence for associations between Parental RF (PRF) and parenting quality (Stuhrmann et al, 2022) has shown mixed results depending on the measures…”
Section: Parental Reflective Functioningmentioning
confidence: 99%
“…A recent review of evidence for associations between Parental RF (PRF) and parenting quality (Stuhrmann et al., 2022) has shown mixed results depending on the measures and contextual factors. An earlier review by Camoirano (2017) identified PRF as a strong predictor of parent‐child relationship quality and secure attachment.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the relationship between parental mentalizing and parental sensitivity has been confirmed in a meta-analysis including N= 2,029 participants and 24 effect sizes (Zeegers, Colonnesi, Stams, and Meins, 2017). Accordingly, a recent systematic review summarizes that the majority of the included 16 studies found small to medium positive associations between parental reflective functioning and parenting quality (Stuhrmann, Göbel, Bindt & Mudra, 2022).…”
Section: Associations Between Parental Reflective Functioning and Par...mentioning
confidence: 99%